Growth and Characterization of Bis(thiourea) Cadmium Acetate Single Crystal: An Efficient Semiorganic Non-linear Optical Single Crystal - Christian Prasana, Johanan; Anuradha, A.; Madhavan, J.; Sagayaraj, P. (Asian Journal of Chemistry, 2012)
Bis(thiourea) cadmium acetate, a metal semiorganic non-linear optical crystal, was synthesized from thiourea and cadmium acetate using double distilled water. The synthesized salt was used to grow bulk size crystals. The XRD analysis confirmed that bis(thiourea)cadmium acetate has orthorhombic crystal structure. The UV transmission study indicates that there is a very low absorption in the visible light region. FTIR analysis suggests the presence of functional groups in the grown crystal. Thermal studies reveal that the grown crystal has considerable thermal stability and it can be exploited for industrial applications. The non-linear optical study confirms frequency doubling of the sample using Nd:YAG laser.